Sexual partnerships of people living with the Human Immunodeficiency Virus - Oliveira, Layze Braz de; Matos, Matheus Costa Brandão; Jesus, Giselle Juliana de; Reis, Renata Karina; Gir, Elucir; Araújo, Telma Maria Evangelista de (Rev Rene, 2018)
Objective: to characterize the sexual partnerships established by people living with the Human Immunodeficiency Virus. Methods: an epidemiological study carried out with 173 participants in a medical assistance service specialized in the treatment of people with Human Immunodeficiency Virus. Data were collected through an individual interview with a specific questionnaire for the study. Pearson’s Chi-square test was used to analyze the data. Results:the majority of the participants were male, young adults (54/30.9%), single (94/53.7%), complete high school (72/41.1%) and sexually infected (150/85.7%). The variables gender (p